13.0k views
3 votes
Please help!! I need the answer and the explanation on how to do this

Please help!! I need the answer and the explanation on how to do this-example-1
User Dan Harris
by
4.7k points

1 Answer

5 votes

Answer:

the first one

Explanation:

y=3x+2

2x+y=-4

becomes

3x+2=y

2x+4=-y

add them

5x+6=0

5x=-6

x=-5/6

take x and replace it for one equation

y=-8/5

User Iolanda
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.